2015
DOI: 10.4161/2162402x.2014.990767
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell vaccine inhibits metastases of primary tumors and induces humoral immune responses against cancer stem cells

Abstract: Keywords: antitumor immunity, cancer stem cell, dendritic cell, metastasis, vaccine Abbreviations: ALDH, aldehyde dehydrogenase; CSC, cancer stem cell; CSC-DC, CSC lysate-pulsed dendritic cell; DC, dendritic cell; H-DC, heterogeneous, unsorted tumor cell lysate-pulsed dendritic cell; RT, radiation therapy; qRT-PCR, real time quantitative PCR.The inability to target cancer stem cells (CSC) may be a significant factor contributing to treatment failure. We have developed a strategy to target the CSC populations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 50 publications
2
70
0
Order By: Relevance
“…22 Abovementioned findings indicated that ALDH1 isoenzymes are also possible therapeutic targets for melanoma. At the same time, Lu et al 23 reported targeting murine MSC via dendritic-cell (DC) vaccination using DCs pulsed with ALDH bright cell lysates, which significantly inhibited tumor growth as compared with DCs pulsed with either ALDH dim or whole tumor lysates. Moreover, in serum from these mice IgG antibodies that bound ALDH bright cells and mediated their complement-dependent lysis were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Abovementioned findings indicated that ALDH1 isoenzymes are also possible therapeutic targets for melanoma. At the same time, Lu et al 23 reported targeting murine MSC via dendritic-cell (DC) vaccination using DCs pulsed with ALDH bright cell lysates, which significantly inhibited tumor growth as compared with DCs pulsed with either ALDH dim or whole tumor lysates. Moreover, in serum from these mice IgG antibodies that bound ALDH bright cells and mediated their complement-dependent lysis were found.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above these antibodies analyzed in animal models were able to eliminate ALDH1 positive melanoma stem cells by antibody dependent cell cytotoxicity. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the absolute number of Tregs was also decreased after vaccination 66 . Additionally, a recent study in a murine model looking at a cancer stem cell (CSC) targeted dendritic cell vaccination showed significantly reduced growth of subcutaneous tumors, increased survival, and decreased pulmonary metastasis 67 .…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…Cancer antigens could be loaded onto DCs by nano-sized carriers including nanoparticles or nanoemulsions (Park et al, 2013). Studies on mice have shown DCs primed by CSCs antigens effectively induced immune response to tumor cells and prolonged survival (Lu et al, 2015;Ning et al, 2012;Xu et al, 2009). Treatment with DCs loaded with CSCs-derived antigen induced a tumorspecific immune response stronger than that induced by DCs loaded with normal tumor cells (Dillman et al, 2012;Jachetti et al, 2013).…”
Section: Cancersmentioning
confidence: 99%
“…DCs are then loaded with cancer antigens by various ways and reinfused into patient (Figure 4). Cancer antigens can be generated from tumor lysates (Yu et al, 2004), apoptotic bodies (Labarriere et al, 2002), peptides (Rosalia et al, 2013), tumor RNAs (Kalady et al, 2004), and tumor-derived exosomes (Mahaweni et al, 2013). Cancer antigens could be loaded onto DCs by nano-sized carriers including nanoparticles or nanoemulsions (Park et al, 2013).…”
Section: Cancersmentioning
confidence: 99%